African Great Lakes Rural Broadband Research Infrastructure - Kahiigi, Peter; Kariuki, Eunice; Kyalo, Victor; Masinde, Muthoni; Ngarambe, Donart; Nungu, Amos; Sansa-Otim, Julianne; Pehrson, Björn (In IST-Africa Conference, 2012)
The African Great Lakes Rural Broadband Research Infrastructure (AGLARBRI) addresses the establishment of sustainable broadband markets in areas where there is demand but no supply of broadband services. The scientific objective is to validate the reproducibility, scalability and extensibility of earlier successful results from the Tanzania ICT for Rural Development program. The development objective is to accelerate the deployment of commercial last mile links by stimulating community based first mile initiatives. Under-served local communities in Kenya, Uganda, Rwanda, Burundi and eastern DRC are being targeted and supported by local research and higher education institutions to support capacity building. Innovative and affordable technical solutions based on off-the shelf hardware and open source software are being packaged for industrial distribution. The application focus is on inclusive ubiquitous access, and basic public services such as Healthcare, education and local administration. The project is well aligned with the new targets from the UN Broadband Commission, which clearly justify the mainstreaming of the results from Tanzania to the other neighbouring countries.
Keywords: ICT4D; Inclusive Ubiquitous Access; eInfrastructures; eAccessibility; Health Information Systems